PERTANIAN SEBAGAI PENOPANG UTAMA EKONOMI MASYARAKAT DESA ALAANG KECAMATAN ALOR BARAT LAUT - Feni Diana Djaha; Salomi Duka; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
This study aims to describe the agricultural potential that serves as the main pillar of the economy of the community in Alaang Village, Alor Barat Laut District. The research employed a qualitative method with interview techniques, using the Head of Alaang Village as the primary data source. The findings indicate that the agricultural sector is the most prominent potential in the village, with main commodities including rice, corn, and various types of vegetables. Rice is the staple crop that plays a very important role for the community, as it serves both as the main food source and an additional source of income. Corn functions as an alternative food source as well as an economic commodity, while vegetables such as mustard greens, spinach, water spinach, bitter melon, cabbage, tomatoes, chili, cucumbers, and eggplants are cultivated for daily consumption and sold when there is a surplus harvest. Agricultural activities are carried out from generation to generation and have become an essential part of the community’s livelihood. Based on these findings, agriculture is a sector that not only supports food security but also drives the economy of Alaang Village.